2010
DOI: 10.1590/s2176-94512010000600016
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo entre traçados cefalométricos manual e digital, através do programa Dolphin Imaging em telerradiografias laterais

Abstract: Objective: The purpose of this study was to compare angular and linear cephalometric measurements obtained through manual and digital cephalometric tracings using Dolphin Imaging ® 11.0 software with lateral cephalometric radiographs. Methods: The sample consisted of 50 lateral cephalometric radiographs. One properly calibrated examiner performed 50 manual and 50 digital cephalometric tracings using eight angular measurements (FMA, IMPA, SNA, SNB, ANB, 1.NA, 1.NB, Y-Axis) and six linear measurements (1-NA, 1-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 9 publications
4
19
0
6
Order By: Relevance
“…This findings is supported by study perfomed by Paixão et.al [36] which compares between manual and automatic process using Dolphin imaging software on 50 subjects (male and female). The study did not show any significance difference between manual and automatic process [36]. Similar findings have been reported by Tikku et al using 13 linear and 13 angular measurements on 40 subjects, where only 6 among 13 measurements were significant [37].…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…This findings is supported by study perfomed by Paixão et.al [36] which compares between manual and automatic process using Dolphin imaging software on 50 subjects (male and female). The study did not show any significance difference between manual and automatic process [36]. Similar findings have been reported by Tikku et al using 13 linear and 13 angular measurements on 40 subjects, where only 6 among 13 measurements were significant [37].…”
Section: Introductionsupporting
confidence: 79%
“…Recent study showed that current cephalometric measurements obtained with the computerized cephalometric systems can be considered reliable, and can be used by the clinician [33, 36, 37]. This findings is supported by study perfomed by Paixão et.al [36] which compares between manual and automatic process using Dolphin imaging software on 50 subjects (male and female). The study did not show any significance difference between manual and automatic process [36].…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…But obviously it was also limited in use as it overlooked the soft tissue thickness variations and longitudinal studies were also impossible. Pacini was the first to attempt standardization in radiography of head in 1922 and then Broadbent in USA and Hofrath in Germany announced their methods of radiography (CM) of skull simultaneously 2 . CM combined the advantages of anthropometry and craniometry, which made it possible to measure craniofacial hard tissues as well as soft tissues.…”
mentioning
confidence: 99%